Jogos e ensino de história: uma proposta de reconhecimento do patrimônio cultural através dos 7 Povos das Missões - Valenzuela, Tainá Severo (2013)
This paper presents the structure and development of an online game that aims to be used as an educational support for teachers, students and other people interested in themes related to the History of Missions in Rio Grande do Sul. The game takes place inciting a critical assessment of their player, in a process where they can understand the history through its society and its cultural relations. This work was triggered by an investigation made in textbooks published by differentes editors in Brazil and in tests applied in competition of Prendas and Peões promoted by Gaucho Traditionalist Movement (MTG) that made us conclude that the history of the Jesuit Missions that unfolded in the territory where today is the Rio Grande do Sul (known as the history of "7 Missionarie People ") has been taught and played in a vulgar way, without exploring the cultural and social procedures which the history has. We demonstrate how we understand the missionary period, within the social relations developed, the specific cultural characteristics of the period, the human condition that pervade it and any historical moment.